Local Fractional Sumudu Transform with Application to IVPs on Cantor Sets - H. M. Srivastava; Alireza Khalili Golmankhaneh; Dumitru Baleanu; Xiao-Jun Yang (Abstract and Applied Analysis)
Local fractional derivatives were investigated intensively during the last few years. The coupling method of Sumudu transform and local fractional calculus (called as the local fractional Sumudu transform) was suggested in this paper. The presented method is applied to find the nondifferentiable analytical solutions for initial value problems with local fractional derivative. The obtained results are given to show the advantages.